Impact of the Koala Project on clinical outcomes of preterm infants in two maternity hospitals - Lorena Dias Dantas; Ricardo Queiroz Gurgel; Verena Pimenta Santos; Debora Fontes Leite; Ikaro Daniel de Carvalho Barreto (Revista Paulista de Pediatria, 2023)
ABSTRACT Objective: To describe the impact of the Koala project (Actively Controlling Target Oxygen) on clinical outcomes in patients born with less than 36 weeks of gestation, in two maternity hospitals, comparing before and after the strategy implementation. Methods: This is an intervention study with 100 preterm infants with gestational age ≤36 weeks, who used oxygen in two maternity hospitals between January 2020 and August 2021. One of the hospitals was a private institution and the other was philanthropic. The goal for the target oxygen saturation with this project was 91–95%. Comparisons between the two stages (before and after the implementation of the project) were made evaluating the outcomes of retinopathy of prematurity, bronchopulmonary dysplasia, necrotizing enterocolitis, and deaths. The continuous variables were described using mean, median, standard deviation and interquartile interval. The significance level adopted was 5% and the software used was R Core Team 2021 (version 4.1.0). Results: After oxygen control use according to the Koala protocol, there was a significant reduction in the cases of retinopathy of prematurity (p<0.001) and bronchopulmonary dysplasia (p<0.001). There were no deaths in the second stage, and there was a non-significant increase in the absolute number of necrotizing enterocolitis cases. Conclusions: The Koala project seems to be an effective and feasible strategy to reduce adverse situations in the management of premature children, but research with a greater sample is needed.